Strengthening Teachers’ Psycho-Spiritual Well-Being through Reflection on Asmaul Husna: A Reflective Phenomenological Approach to Teacher Emotion Regulation in Resource-Limited Settings - Puji Astuti Indraningsih; Muhammad Iqbal (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Teacher well-being is a critical issue in contemporary education, particularly in resource-limited schools that demand high levels of emotional regulation. Although reflective practice and emotion regulation have been widely studied, research on Islamic values-based psycho-spiritual microinterventions remains limited, especially qualitative studies that explore teachers’ lived experiences within the context of inclusive education in Indonesia. This study aims to explore brief reflective practices based on the Asmaul Husna Ar-Ra’ūf, Ar-Raḥīm, and Al-Wadūd as psycho-spiritual micro-interventions to support teachers’ emotional regulation and well-being. Employing a reflective phenomenological approach, this study involved six teachers from a dhu’afa school in Bali. Data were collected through reflective journals and in-depth interviews and analyzed using reflective thematic analysis. The findings identified four main themes: calming, gentle emotional regulation; rahmah, the strengthening of pedagogical care; love, the revitalization of professional meaning; and emotional recovery through enhanced spiritual awareness. These findings highlight the study’s original contribution by addressing a gap in the literature on contextual, low-cost, and easily integrated Islamic values-based micro-interventions to support teacher well-being in resource-limited educational settings. Keywords: Asmaul Husna, emotion regulation, psycho-spirituality, reflective practice, teacher well-being